STEP Support Programme STEP 2 Trigonometry Questions: Solutions
STEP Support Programme STEP 2 Trigonometry Questions: Solutions
STEP Support Programme STEP 2 Trigonometry Questions: Solutions
org/step
1 We have
cos 3x = cos 2x cos x − sin 2x sin x
= (2 cos2 x − 1) cos x − (2 sin x cos x) sin x
= 2 cos3 x − cos x − 2 cos x sin2 x
= 2 cos3 x − cos x − 2 cos x(1 − cos2 x)
= 2 cos3 x − cos x − 2 cos x + 2 cos3 x
= 4 cos3 x − 3 cos x
Since the answer is given, you do need to show every step. Remember “One equal sign per
line, all equal signs aligned”!
Similarly, using sin 3x = sin 2x cos x + cos 2x sin x leads to sin 3x = 3 sin x − 4 sin3 x.
= − cos α − 23 cos 3α − −1 − 32
= −c − 23 (4c3 − 3c) + 5
3
= − 38 c3 + c + 5
3
I(α) =
R 00 when c = 1 (this can be easily found, as when α = 0 the integral is of the
form 0 f(x) dx = 0 giving cos(0) = 1).
Z α
7 sin x − 8 sin3 x dx
J(α) =
70 2 α
= 2 sin x − 2 sin4 x 0
7 2 4
= 2 sin α − 2 sin α
2
= 7
2 (1 − cos α) − 2(1 − cos2 α)2
= −2c4 + 12 c2 + 32
You can then substitute c = cos(β) = − 61 and show that I(β) = J(β), but this is a
little fiddly (there are fractions with denominator 648 involved). Another way is to
show that 6c + 1 is a factor of the equation you get by solving I(α) = J(α). Remember
that for a “Show that” you must fully support your answer.
− 38 c3 + c + 5
3 = −2c4 + 12 c2 + 3
2
12c4 − 16c3 − 3c2 + 6c + 1 = 0 (*)
If you have already substituted c = − 61 into I(α) and J(α) and shown that this is a
solution then you can factorise out (6c + 1) without further explanation of why you
can do it.
Otherwise, you can:
• substitute c = − 16 into (∗) and show that this is a solution (this is not too bad,
especially if you don’t evaluate 63 )
• use long division to show that (6c + 1) is a factor (remember to show that the
remainder is 0 in this case)!
• factorise out (6c + 1) by inspection and then expand the brackets to show that
this works.
In each case you do need to end by stating something like “Hence c = cos(β) = − 16
gives Eustace the correct value of I(β)”.
The equation fully factorises to give (6c+1)(2c+1)(c−1)2 = 0, so we have cos α = − 16 ,
cos α = − 12 and cos α = 1. There are no given restrictions on α, so we need the general
solutions1 . These are:
cos α = 1 =⇒ α = 2nπ
cos α = − 21 =⇒ α = 23 π + 2nπ or α = − 23 π + 2nπ
cos α = − 61 =⇒ α = cos−1 − 6 + 2nπ
1
α = − cos−1 − 16 + 2nπ
or
1
See the topic notes.
2 There are two basic approaches for the first identity. Starting on the LHS gives:
tan π4 − tan x2
π x
tan 4 − 2 ≡
1 + tan π4 tan x2
1 − tan x2
≡
1 + tan x2
cos x2 − sin x2
Multiplying top and bottom by cos x2
≡ x
x
cos 2 + sin 2
cos x2 − sin x2 cos x2 − sin x2
≡
cos x2 + sin x2 cos x2 − sin x2
1 − 2 sin x2 cos x2
≡
cos2 x2 − sin2 x2
1 − sin x
≡
cos x
≡ sec x − tan x
Alternatively you can start on the RHS and use the t = tan 21 A formulae from the formula
book (with A = x):
1 + t2 2t
sec x − tan x ≡ −
1 − t2 1 − t2
(1 − t)2
≡
(1 − t)(1 + t)
1−t
≡
1+t
1 − tan x2
≡
1 + tan x2
≡ tan π4 − x2
π
(i) Setting x = 4 into the identity from the stem gives:
√
tan π4 − 12 × π4 = sec π4 − tan π
4 = 2 − 1.
11
Then note that 24 π = 18 π + 13 π which gives:
tan 81 π + tan 13 π
1 1
tan 8π + 3π =
1 − tan 18 π tan 13 π
√ √
2−1+ 3
= √ √
1 − ( 2 − 1) 3
√ √
3+ 2−1
=√ √ as required.
3− 6+1
(ii) Since 2
√ the√ answer
is given
√ here,
√ you √ can√
multiply
√ across and verify that
3 − 6 + 1 2 + 2 + 3 + 6 = 3 + 2 − 1.
2
In this case verify means “expand the brackets and show it is true”. You MUST show all the working here as it
is a “show that”. A table might be a nice clear way of showing your working.
You should show a few more lines of working than presented here.
You then need to carefully expand the squared bracket (I would recommend a table
for doing this) to get to the required result.
3
If you had not been given the answer this is probably the approach you would have had to take. The first
approach probably has less room for error though!
Since this result is in the “stem” of the question, you should expect to use it at least once
(and probably more often) in the following question parts.
The last step came from using cos 2A = cos2 A − sin2 A, sin 2A = 2 sin A cos A and
cos2 A + sin2 A = 1.
(ii) Using the substitution t = tan 12 x in the same way as in part (i)(b) results in the
Z π
1 2 cos x
integral dx.
2 0 1 + 3 sin2 x
√
A further substitution of y = 3 sin x gives the integral:
Z √3
1 1 1 √ 3
√ dy = √ arctan y 0
2 3 0 1 + y2 2 3
1 π 1
which gives the final answer as √ × = √ π.
2 3 3 6 3
4 This is quite a long question (and in my opinion quite a hard one) as there is a lot going
on.
(i) Using cos θ = sin(90◦ − θ) gives us sin(90◦ − θ) = sin 4θ. There is one obvious solution
i.e. 90◦ − θ = 4θ =⇒ θ = 18◦ . However the question asks for all the values of θ, so
there are almost certainly some more.
Using the periodicity of sin x we have:
90◦ − θ = 4θ + 360◦ =⇒ θ = −54◦ out of range
◦ ◦ ◦
90 − θ = 4θ − 360 =⇒ θ = 90 OK
◦ ◦ ◦
90 − θ = 4θ − 720 =⇒ θ = 162 OK
◦ ◦ ◦
90 − θ = 180 − 4θ =⇒ θ = 30 OK
◦ ◦ ◦
90 − θ = 540 − 4θ =⇒ θ = 150 OK
As is usually the case, a sketch helps make sure that you have all the possible values.
You can also do this by solving cos θ = cos(90◦ − 4θ) and it might be a useful exercise
to check that you get the same answers trying this method.
To find sin 18◦ we use the double angle formulae to get:
cos θ = 2 sin 2θ cos 2θ
cos θ = 4 sin θ cos θ × 1 − 2 sin2 θ .
Then either cos θ = 0 (which is rejected as we are after θ = 18◦ ) or 1 = 4 sin θ −8 sin3 θ.
It is usually helpful to write sin θ = s so the equation is 8s3 − 4s + 1 = 0.
To solve this cubic, first note that θ = 30◦ will be a solution (from above), so s = 12 is
a solution (which we will reject as we want θ = 18◦ ). Using this to factorise we get:
8s3 − 4s + 1 = (2s − 1)(4s2 + 2s − 1) = 0 .
Using the quadratic formula gives the other two solutions as:
√ √
−2 ± 20 −1 ± 5
s= = .
8 4
√
The final step is to notice that sin 18◦ will be positive, so sin 18◦ = 1
4 5−1 .
Using sin x = s gives the quartic equation 16s4 − 12s2 + 1 = 0. We can solve this for
s2 giving √ √ √
2 12 ± 144 − 4 × 16 3± 9−4 3± 5
s = = = .
2 × 16 8 8
(iii) This is a “hence” question, so we need to refer to the previous parts (and trying to do
it another way will probably gain no credit). If we take the equation from part (ii)
and divide by 4 we get:
sin2 x + 41 = sin2 2x .
If we then take 3α = x and 5α = 30◦ then this is the same as the equation in part
(iii). 5α = 30◦ gives α = 6◦ which gives x = 18◦ which is a solution to part (ii).
Finding the second solution is a little trickier. If we are to use the equation in part (ii)
then we need sin 5α = ± 12 . We also want probably want x to be “related” to 18◦ .
A bit√of trial and error is needed, but if we take x = 180◦ + 18◦ then we have sin x =
− 14
5 − 1 , which is a solution to the equation in part (ii).
◦
This means α = 198 ◦ ◦ 1
3 = 66 which gives 5α = 330 and so this satisfies sin 5α = − 2 .
Hence a second solution is α = 66◦ .